Pengaruh Supervisi Akademik Kepala Sekolah, Disiplin Kerja Guru, Dan Komunitas Belajar Terhadap Kompetensi Pedagogik Guru - Poyo Poyo; Bunyamin Bunyamin; Muhammad Prayito (Cetta: Jurnal Ilmu Pendidikan, 2026)
The background of this study is the low pedagogical competence of junior high school teachers in Blora District, Blora Regency. Factors suspected of influencing teacher pedagogical competence include principal academic supervision, teacher work discipline, and learning community. This study aims to determine the magnitude of the influence of principal academic supervision, teacher work discipline, and learning community on the pedagogical competence of junior high school teachers in Blora District, Blora Regency. The study used a quantitative approach with an ex post facto design. The study population was all junior high school teachers in Blora District, Blora Regency, with a sample of 153 teachers determined using proportional random sampling technique. Data collection was carried out through a closed questionnaire. Data analysis included tests of normality, linearity, homogeneity, multicollinearity, simple regression, and multiple regression. The results of the study showed that: (1) principal academic supervision had a significant effect on teacher pedagogical competence by 56.3%; (2) teacher work discipline had a significant effect on teacher pedagogical competence by 58.0%; (3) learning communities have a significant influence on teachers' pedagogical competence by 64.9%; and (4) the principal's academic supervision, teachers' work discipline, and learning communities simultaneously have a significant influence on teachers' pedagogical competence by 66.1%. The novelty of this research lies in the integrative testing of the influence of academic supervision, work discipline, and learning communities on teachers' pedagogical competence.